Seed Preservation Practices in the Tamang Community: An Ethnographic Study in the Tamang Community of Namobuddha, Kavre - Lamsal, Saurav (Journal of Multidisciplinary Research Advancements, 2026)
Indigenous seed preservation and practices are deeply rooted in cultural traditions, ensuring seeds are passed down through generations. This study aims to explore how the Tamang community preserves seeds within their local community. A qualitative study was undertaken using observation and key informant interviews with people of different ages in ethnographic settings. The field inquiry involves sun-drying followed by storage in fibre bags and metal containers, with preservation using titepati leaves, which not only maintains seed quality but also reflects cultural identity. Local and traditional seed banks are in practice. By focusing on the Tamang community, this research puts the value of indigenous knowledge of seed preservation in promoting food security. However, the shift towards modern seeds endangered the community's traditional agricultural systems. This paper describes how the people of the Tamang community in Namo Buddha municipality used to preserve the seeds. Indigenous seed preservation practices are slowly shifting towards modern agricultural systems. Despite the threat posed by modern agricultural systems, these local systems play a vital role in preserving local crops.